2008
DOI: 10.1016/j.trstmh.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis assemblage, clinical presentation and markers of intestinal inflammation in Brazilian children

Abstract: SummaryData on the relationship between the two genotypes of Giardia duodenalis that infect humans, assemblages A and B, their clinical presentation and intestinal inflammation are limited. We analyzed 108 stool samples previously collected for a diarrhoeal study among Brazilian children, representing 71 infections in 47 children. Assemblage B was most prevalent, accounting for 43/58 (74.1%) infections, while assemblage A accounted for 9/58 (15.5%) infections and 6/58 (10.3%) infections were mixed (contained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
98
2
15

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 30 publications
15
98
2
15
Order By: Relevance
“…Similar results were observed in Bangladesh, Spain and Portugal, with a significant association between genotype A and symptomatic infection being reported [104,107]. Unlike the above mentioned studies, some reports have not found a correlation between genotype and clinical presentation of giardiasis [102].…”
Section: Genotype-clinical Presentation Relationshipsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were observed in Bangladesh, Spain and Portugal, with a significant association between genotype A and symptomatic infection being reported [104,107]. Unlike the above mentioned studies, some reports have not found a correlation between genotype and clinical presentation of giardiasis [102].…”
Section: Genotype-clinical Presentation Relationshipsupporting
confidence: 77%
“…Several studies have suggested that the variability of symptoms of giardiasis would be mediated by the host immune response. A longitudinal study in endemic areas of Brazil indicated that individuals previously infected with Giardia were less prone to symptomatic reinfection than individuals who were never exposed to the parasite [102]. Our research group has observed that the frequency of symptomatic giardiasis in schoolchildren in the province of Buenos Aires diminished as age increased [47,48].…”
Section: Clinical Presentationmentioning
confidence: 68%
“…29 Several studies have been conducted using 18S rRNA markers. However, although it is an excellent marker, gdh has higher variability and allows for the subtyping within assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Durante nuestro estudio no se tuvo en cuenta la sintomatología del paciente, por lo cual no se pudo hacer una correlación entre el genotipo y las manifestaciones clínicas, como sí lo han hecho otros autores (36,37).…”
Section: Figuraunclassified